The role of People's Universities in ecological education of country youth - Aptacy, Janusz (Studia Ecologiae et Bioethicae, 2007)
This article concerns widely perceived ecological education being provided among country youth by People’s Universities, their homeland is Denmark and M. F. S. Grundvig is concerned to be their father. He observed English educational system and the way of education with the usage of boarding schools and then he transmitted it to Denmark, where at the end of the 18th c. and at the beginning of the 19th century the role of peasants, who reached for power and had their own farms, increased, therefore, there was a necessity to create an integrated educational system for those people. Thiss way of educating was then carried to Poland by Ignacy Solarz and his wife Zofia Solarzowa - that took place in the mid-20th century. A special tribute of these educational institutions was reaching those country groups of people who were hungry for knowledge and social advance. People’s Universities had and have ecological education established in their educational programme. However, this education concerns integrated, harmonic and balanced development of the human being, since, if ecology means the knowledge about the environment, it is the human being that should be the most important, that should be the subject. In this system of educating one is not only concerned in gaining the knowledge, but also in ability to pass the gained knowledge, expressing one’s opinions, ability to make relations with people and with the world. This system is about the most integrated development of a student’s personality, the ecological education must not limit itself just to care about the nature, but it should also take into consideration the human’s psychology, environment in which one was brought up and also the values with which one was fed. That is why this widely taken ecology should not omit religious, cultural and patriotic values. And People’s Universities draw their attention to this kind of values.